The Association Between Peritoneal Charge Barrier Dysfunction and Protein Lost During Continuous Ambulatory Peritoneal Dialysis - Guo-Qing Yu; Jian Chen; Jun-Xia Li (Karger Publishers, 2013)
Background/Aims: The main purpose of the present study was to determine the effect of peritoneal charge barrier dysfunction on hypoalbuminemia during CAPD. Methods: We measured the association of dialysis dose, peritoneal equilibration test (PET) results (ratio of dialysate and plasma creatinine), and peritoneal charge barrier index (ratio of pancreatic and salivary α-amylase clearance) on protein loss in 33 patients on maintenance CAPD. All patients were from a single institution and were diagnosed with chronic nephritis (n = 18 cases), diabetic nephropathy (n = 8), hypertension (n = 5), and hepatitis B virus-associated glomerulonephritis (n = 2). Results: The mean (± SD) dialysate protein loss was 4.04 g (± 1.97) per day. Protein loss was positively correlated with dialysis dose (r = 0.438, p = 0.01) but was not significantly correlated with PET results. The mean (± SD) peritoneal charge barrier index was 6.12 (± 21.20) and was inversely correlated with protein loss into the peritoneal dialysate (r = -0.532, p Conclusions: Taken together, our study of CAPD patients indicates that protein loss into the peritoneal dialysate increases with peritoneal dialysis dose and with disruption of the peritoneal charge barrier.